Influence of irrigation and nitrogen levels on yield attributes, yield and water use efficiency in dill (Anethum graveolens L.) cultivation: Irrigation and nitrogen levels in dill cultivation - Bairwa, R C; Bhunia, S R (Journal of Spices and Aromatic Crops, 2023)
The field experiments were conducted during three consecutive Rabi seasons of 2016-19 at Agricultural Research Station, SKRAU, Bikaner to study the influence of irrigation and nitrogen levels to growth, yield attributes, yield and water use efficiency of dill (Anethum graveolens L.) under a drip irrigation system. The experiment consisted of sixteen treatment combinations of four irrigation levels (ETc- 0.4, ETc- 0.6, ETc- 0.8 & ETc- 1.0), & four nitrogen levels (control, 120% RDN in 4 splits, 100% RDN in 4 splits and 80% RDN in 4 splits). The treatments were laid out in a split plot design with three replications. Results revealed that irrigation at ETc 1.0 with application of nitrogen at 120% of RDN in four splits recorded significantly higher crop yield as compared to the remaining treatments. The water use efficiency decreased with increased irrigation and nitrogen levels.